Surgical treatment of primary cardiac tumors: 20-year single center experience - Děrgel, Martin; Gofus, Ján; Smolák, Petr; Stejskal, Václav; Hanke, Ivo; Matějka, Jan; Manďák, Jiří; Vojáček, Jan (Kardiochirurgia i Torakochirurgia Polska, 2022)
Introduction: Primary cardiac tumors are a rare condition presenting with a variety of symptoms. The outcomes of their surgical treatment in the modern era from central Europe have not been recently reported. Aim: To evaluate the short- and long-term outcomes of the cardiac tumor operations at our department throughout the last 20 years. Material and methods: This was a retrospective analysis of all primary cardiac tumor operations performed at our institution between 2000 and 2020. Perioperative data were extracted from patient records. Long-term data were provided by the National Registry of Cardiac Surgery. Results: Sixty procedures for primary cardiac tumor were performed throughout the study period. The most common type of tumor was myxoma (88%), followed by fibroelastoma (8%), lipoma (2%) and sarcoma (2%). There were 2 perioperative deaths (3%). The most common perioperative complication was atrial fibrillation (47%). One (2%) patient underwent reoperation 6 years later because of myxoma recurrence. We recorded 13 long-term deaths, but only 1 patient died as a consequence of cardiac tumor (sarcoma) 15 months after the surgery. Long-term survival of the cohort was comparable with the age- and sex-matched general population up to 15 years postoperatively (relative survival 0.91, CI 0.68-1.23). Rich histopathological illustrations are provided in the online supplementary material. Conclusions: Surgical resection is the standard treatment of primary cardiac tumors. The outcomes of benign tumors are excellent and the long-term postoperative survival is comparable with the general population. The prognosis of malignant tumors remains poor.